2018
DOI: 10.1590/s2175-97902018000418008
|View full text |Cite
|
Sign up to set email alerts
|

The appropriate use of human albumin in a Brazilian University Hospital: therapeutic indication and dosage regimen

Abstract: The objective of the study was to evaluate the use of human albumin in a Brazilian university hospital, in compliance with the institutional protocol and other clinical guidelines, taking into account the therapeutic indications and the dosage regimens. Data was obtained from the pharmacy dispensing records of human albumin, the requests for use it and, when available, the patient's records between January and October 2017. After evaluation the therapeutic indications and the dosage regimens were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These include; management of malnutrition in critically ill patients, nephrotic syndrome not associated with hypovolemia and/or pulmonary edema, ascites responsive to diuretic therapy and pancreatitis (Liumbruno et al, 2009;Caraceni et al, 2013;Farasatinasab et al, 2018). Several studies have reported albumin misuse in the literature, showing its negative clinical and economic impacts (Lyu et al, 2016;Zolfagharian et al, 2017;Dastan et al, 2018;Ishida et al, 2018;Javan-Noughabi et al, 2020). This misuse could be attributed to absence of collective protocols defining appropriate albumin indications to guide healthcare providers, and also the lack of restrictive dispensing in the clinical setting (Buckley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These include; management of malnutrition in critically ill patients, nephrotic syndrome not associated with hypovolemia and/or pulmonary edema, ascites responsive to diuretic therapy and pancreatitis (Liumbruno et al, 2009;Caraceni et al, 2013;Farasatinasab et al, 2018). Several studies have reported albumin misuse in the literature, showing its negative clinical and economic impacts (Lyu et al, 2016;Zolfagharian et al, 2017;Dastan et al, 2018;Ishida et al, 2018;Javan-Noughabi et al, 2020). This misuse could be attributed to absence of collective protocols defining appropriate albumin indications to guide healthcare providers, and also the lack of restrictive dispensing in the clinical setting (Buckley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%